Correlation of SARS-Cov2 viral load with severity of COVID-19 disease in pregnant women at term: an observational study - Batra, Sapna; Malhotra, Anuradha; Oberoi, Loveena; Singh, Kamal Deep; Mohindroo, Babica (International Journal of Research in Medical Sciences, 2023)
Background: COVID-19 disease raised global health concerns especially for the pregnant women who are more susceptible to respiratory viral illnesses due to their bodily immunological and physiological changes to accommodate the foetus. The aim of the study is to evaluate the relationship between the SARS-CoV 2 specific RdRp gene Ct values ​​and the severity of the COVID-19 disease in SARS-CoV2 positive pregnant women at term. Methods: A retrospective cohort study was conducted in the Department of Microbiology, Government Medical College, Amritsar on a subset of 46 COVID-19 positive, ante natal mothers, who presented in the labour room for delivery from August 2020 to January 2022. Results: A cohort of 4.8% (46/949) women tested positive in the RT-PCR test for viral RNA. Average age of the group was 25.5years and 89.1% were asymptomatic. 10.9% women reported mild symptoms and 95% had no pre-existing co morbidities. Obstetric complications like premature rupture of membranes were 4.3%, pre-term births 17.33%. Miscarriage and IUD was recorded in 4.34% and 2.17% patients respectively. When compared to values seen in symptomatic women with fever (Ct 25.8), dyspnoea (Ct 28.7), and respiratory distress (Ct 29.1), the mean Ct value reported in asymptomatic women (27.49 SD+5.4) was identical. SARS-CoV2 was not present in any newborns. Despite 24% having low birth weights for their gestational ages, 93% of babies were asymptomatic. Conclusions: The severity of the COVID-19 illness did not correspond with the SARS CoV2 virus RdRp gene Ct levels. The presence of SARS-CoV2 did not appear to independently cause poor maternal and new-born outcomes.